2009
DOI: 10.3171/2008.3.jns17459
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers relating to malignant progression in Grade II astrocytoma

Abstract: Overexpression of TP53, TP53 mutation, and Ki 67 labeling index could be molecular markers in astrocytomas predicting malignant progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Authors of several recent studies have examined the histological grade and molecular alterations in order to identify biomarkers for predicting malignant progression. In a study of 33 WHO grade II astrocytomas by Yue et al [15], expression of Ki-67 was significantly associated with malignant progression, suggesting that tumors expressing higher Ki-67 may have an inherently faster growth rate and thus recur faster in the setting of gross-total or subtotal resection. Ishii et al reported that the presence of TP53 mutation in WHO Grade II astrocytoma was associated with malignant progression and shorter PFS, whereas tumors without TP53 mutation recurred and progressed to malignancy without the change in TP53 status [16].…”
Section: Discussionmentioning
confidence: 99%
“…Authors of several recent studies have examined the histological grade and molecular alterations in order to identify biomarkers for predicting malignant progression. In a study of 33 WHO grade II astrocytomas by Yue et al [15], expression of Ki-67 was significantly associated with malignant progression, suggesting that tumors expressing higher Ki-67 may have an inherently faster growth rate and thus recur faster in the setting of gross-total or subtotal resection. Ishii et al reported that the presence of TP53 mutation in WHO Grade II astrocytoma was associated with malignant progression and shorter PFS, whereas tumors without TP53 mutation recurred and progressed to malignancy without the change in TP53 status [16].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Owing to the indistinct symptoms and lack of an effective diagnostic method for early detection, patients with GC are typically diagnosed at an advanced stage and have a dismal prognosis. 5,6 Taking this into consideration, it is necessary to seek more effective biological markers for the diagnosis and treatment of GC. 5,6 Taking this into consideration, it is necessary to seek more effective biological markers for the diagnosis and treatment of GC.…”
Section: Introductionmentioning
confidence: 99%
“…They found that overexpression of TP53 protein was related to malignant progression. In our previous study, we reported TP53 overexpression and mutation as molecular markers to predict malignant progression in astrocytomas[19]. However, the role of TP53 in predicting prognosis for LGGs is controversial.…”
Section: Discussionmentioning
confidence: 99%